The Using of PAKEM Approach in the Students’ Learning English Activity - Wahab, Isnaeni (Edu-Ling: Journal of English Education and Linguistics, 2018)
This study was aimed to know the teaching method of teacher, and to know the active learning of students in the classroom. The research method used in this research was descriptive study. The population of this research was the sixth grade of SD Kartika XX-I Makassar with the sample consist of 26 students. Data collection is taken by giving test. The students were asked to rearrange the picture in groups. The results found that the method used by teachers is PAKEM method. The result of the average score is 75.05 with standard deviation of 16.2. It is known that the range of values of 80-100 are 7 people (26.9%) with excellent category, 66-79 ranges of 6 (23.1%) with good category, the range of values 56-65 is 3 (11, 5%) with moderate category, 40-55 value ranges were 6 persons (23.1%) with the category of less, 30-39 score range was 4 persons (15,4%) with failed category. It can be concluded that student activeness in class is good.